2022
DOI: 10.1371/journal.pone.0271996
|View full text |Cite
|
Sign up to set email alerts
|

Physiological reactions to acute stressors and subjective stress during daily life: A systematic review on ecological momentary assessment (EMA) studies

Abstract: Objective This review aims to provide an overview of ecological momentary assessment (EMA) studies analyzing stress reactivity during daily life in terms of direct and moderated influence of acute stress on physiological responses. Materials and methods A systematic literature search was performed on November 29, 2021 using Web of Science, MEDLINE and PsycINFO to identify prospective EMA studies targeting acute stressors or stress under naturalistic conditions, without restrictions of publication date or pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 193 publications
(369 reference statements)
0
16
0
Order By: Relevance
“…Field studies examining these relationships in naturalistic settings have demonstrated the importance of measuring BP and stress in daily life (e.g., (8)). However, these studies often have small sample sizes or short study duration (e.g., 24 hours or a few days) (9,10), given the difficulty to scale up the collection of physiological data.…”
Section: Introductionmentioning
confidence: 99%
“…Field studies examining these relationships in naturalistic settings have demonstrated the importance of measuring BP and stress in daily life (e.g., (8)). However, these studies often have small sample sizes or short study duration (e.g., 24 hours or a few days) (9,10), given the difficulty to scale up the collection of physiological data.…”
Section: Introductionmentioning
confidence: 99%
“…Although everyone responds to stress in some way, everyone's response to stress is highly different. When faced with a significant distress, some people experience a rapid increase in heartbeat, while others have stiffness event cinching in the belly (Johansson et al, 1996;Weber et al, 2022). Stress is a necessary component of life, and a person cannot avoid it easily because they suffer from different situation in their lives (Rux et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This care in terminology is particularly important for eyewitness studies, which often involve complex scenarios that likely produce many other effects, including the impact of arousal, divided attention, perceptual phenomena, or cognitive load. More studies examining links between self-reported levels of stress and physiological states of stress would be helpful for improving the construct validity of self-report measures, and in turn, will improve application to reality (e.g., Weber et al, 2022). Pezdek and Reisberg (2022) also discredited the (ecological) validity of stress induced by the Trier Social Stress Test (TSST; see footnote 2 on p. 146).…”
Section: Discussionmentioning
confidence: 99%